Role of varicocelectomy in improving fertility in infertile male with varicocele - Y. Hassan, Hassan (Journal of Madenat Alelem University College, 2019)
Introduction: Infertility is considered one of the major health problems. 40%–50% of infertility cases are associated with the male factor. There are several types of male infertility. From all types of male infertility, idiopathic infertility and varicocele are the major types. In general population, varicocele has an incidene of 4.4%-22.6%. The surgical treatment is varicocelectomy which can be performed through subinguinal, transinguinal, or suprainguinal incision. Varicocelectomy can be done either by open, laparoscopic, microscopic, or embolization unilaterally or bilaterally. The aim of the study is to assess effect of varicocelectomy in improving fertility in infertile male with varicocele. Patients and methods: The study was conducted between beginning of March to the end of October 2017. Twenty one (21), infertile male patients with varicocele were collected randomly. The diagnosis of varicocele was done clinically and by doppler ultrasonography. Clinical diagnosis was done by one surgeon and Doppler was conducted by one ultrasonographer. Seminal fluid analysis (SFA) and hormonal assay (Testesterone, FSH, LH and prolactine) were done for patient in initial diagnosis in the same laboratory using mini-vidas automated hormone analyzer. Scrotal subinguinal approach was used for performing varicocelectomy. Postoperatively, SFA was repeated monthly for assessment of patient improvement for 3 months. Results: 21 infertile men with varicocele included in this study and the mean of age of patients were 31.4 ± 9.7 years. Postoperatively, all parameters included in this study improved in a highly significant matter (P <0.001).Conclusion: This study showed that varicocelectomy improves the fertility of infertile males with varicocele.